Inovasi Pengembangan dan Peningkatan Nilai Tambah Buah Salak sebagai Produk Eksport pada KWT Agro Abian Salak di Desa Sibetan Karangasem - Ida Ayu Elistywati; Made Satria Pramanda Putra; Ni Wayan Merry Nirmala Yani; Putu Yunita Wacana Sari (Yayasan Pondok Pesantren Sunan Bonang Tuban, 2026)
This community service program aims to improve the welfare of rural communities through the development of local economic potential, focusing on innovation and increasing the added value of salak (snake fruit) as an export product. The method used was descriptive qualitative, derived from interviews and training. Secondary sources were obtained from scientific journals, books, and relevant documents, which were then described. The results of this community service program demonstrate an improvement in the quality of the snake date product. The processing of the salak dates involves several stages, and after additional fermentation and oven drying, the water content is reduced from 39.5 to 18.8. This low water content allows the salak dates product to be consumed longer and meets the 1996 Indonesian National Standard (SNI) limit of 35% for wet food products